Um ambiente computacional de alto desempenho para cálculo de deslocamento usando correlação de imagens digitais. - Várady Filho, Christiano Augusto Ferrario (2016)
This work proposes a high performance computing environment using digital image correlation techniques to determine physical quantities associated with engineering problems. Software ar- chitecture supports this computing environment, integrating several advanced technologies for calculation of displacement and strain ﬁelds of structural elements from testing. The method- ology applies the study of concepts, formulations and techniques for image processing, digital image correlation, high performance computing and software architecture. The methodology also includes speciﬁc procedures in a single environment for the evaluation of physical quanti- ties. Among the main procedures used in the presented software architecture, one can cite the digital image correlation techniques known as Full-Field and Subset, non-linear optimization methods and two-dimensional interpolations. In addition, high performance computing strate- gies are included into the computing environment to achieve performance speed-ups on evalu- ating the displacement ﬁelds using digital image correlation. Comparisons with Scale Invariant Feature Transform and Q4-DIC are also evaluated. Following, the development of a computer prototype has the purpose of validating the presented high performance environment, allowing the calculation of physical quantities in structural elements through the correlation of digital images. Then, submission of case studies into the prototype validates data acquired from tech- nologies built into the prototype, including quantitative analysis of results and measurement of computational time.